2017
DOI: 10.4338/aci2017050078
|View full text |Cite
|
Sign up to set email alerts
|

The International Classification of Functioning, Disability and Health (ICF) in Electronic Health Records

Abstract: Different approaches and technical solutions exist for integrating the ICF in EHRs, such as combining the ICF with other existing standards for EHR or selecting ICF codes with natural language processing. Though the use of the ICF in EHRs is beneficial as this review revealed, the ICF could profit from further improvements such as formalizing the knowledge representation in the ICF to support and enhance interoperability.Citation: Maritz R, Aronsky D, Prodinger B. The International Classification of Functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For functioning to play a role in clinical practice-either in assessment, goal-planning, outcomes, and evaluation-work needs to be done on standardized clinical reporting of the functioning information (20,21). The case needs to be made, to the satisfaction of health policy-makers, that functioning information should be fully integrated into health information systems (22,23), potentially within electronic health records (24). Although the groundwork for using ICF as an international reference framework for functioning information has been laid, the challenge remains to break down the barriers to an increased demand for functioning information from clinical and a recognition on the part of policy makers of the need for routine collection of functioning information in order to strengthening rehabilitation within the health system.…”
Section: Icf As Reference Framework For Functioning Informationmentioning
confidence: 99%
“…For functioning to play a role in clinical practice-either in assessment, goal-planning, outcomes, and evaluation-work needs to be done on standardized clinical reporting of the functioning information (20,21). The case needs to be made, to the satisfaction of health policy-makers, that functioning information should be fully integrated into health information systems (22,23), potentially within electronic health records (24). Although the groundwork for using ICF as an international reference framework for functioning information has been laid, the challenge remains to break down the barriers to an increased demand for functioning information from clinical and a recognition on the part of policy makers of the need for routine collection of functioning information in order to strengthening rehabilitation within the health system.…”
Section: Icf As Reference Framework For Functioning Informationmentioning
confidence: 99%
“…Many studies have demonstrated the potential of automated and semi-automated ICD coding systems, using NLP methods, to streamline medical coding processes (35)(36)(37). Growing integration of the ICF into clinical and research settings, from primary care (38) and EHR implementation (39) to pediatric research (40), present similar opportunities to smooth the adoption and practical use of ICF codes with NLP-based coding systems. Vreeman and Richoz (41) describe potential benefits to both clinical care and research from integrating the ICF and other standardized vocabularies into EHRs, and Bettger et al (42) highlight the role of EHR data in providing key insights to advance quality measures, research, and policy for rehabilitation.…”
Section: Broader Implications Of Icf Coding With Nlpmentioning
confidence: 99%